THE ANALYSIS OF THE TEACHER-MADE TEST FOR SENIOR HIGH SCHOOL AT STATE SENIOR HIGH SCHOOL 1 KUTACANE, ACEH TENGGARA - Lukmanul Hakim; Irhamsyah Irhamsyah (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2020)
This study was designed to find out whether or not the English test made by the teacher called a teacher-made test was valid at state senior high school (SMAN) 1 Kutacane. The research design of this study was a qualitative descriptive research. The description is based on the test made by the teacher or the final test question sheet applied by the teacher for the second year students of senior high school 1 Kutacane. To make it easy to analyse, rubric (the points about the syllabus and lesson plan) and interview were applied. In analyzing the data, the technique applied was a documentary analysis technique ( the final question sheet of English test made by the teacher) and was based on the curriculum as a benchmark to find out the validity of test questions made by the English teacher. Based on the results of research, it was foud out that 92% of questions made by teachers was valid and 8% was invalid. These results indicated that the questions made by the English teacher of state senior high school 1 Kutacane were mostly valid and were in accordance with the curriculum. So, the English teacher of senior high school 1 Kutacane had made valid questions and the level of validity made by the teacher demonstrates the ability of teachers to design questions in English.